Are our competencies revealing our weaknesses? A critique of community psychology practice competencies - Dzidic, Peta; Breen, Lauren; Bishop, Brian (Vincent T. Francisco, Ed. & Pub., 2013)
In this paper we argue that the focus on the development and application of practice competencies for community psychology runs the risk of being a distraction from good practice. We outline three areas that demonstrate the inherent flaws in focusing on traditional notions of competencies for community psychology – the limitations of competencies themselves, the schism between competencies and ethics, and the disconnect between competencies and applied practice. In opposition to traditional notions of competencies underpinned by positivist and mechanist notions, we propose that the distinction between virtue and procedural ethics provides a model for comparing and contrasting virtue and procedural competencies. Virtue competencies provide an orientation and value-base that may be applied to any context in which community psychologists work; in this way, competencies may be positioned as tools for understanding, rather than as understandings.